+0  
 
+1
1
36
1
avatar

1.
f(x)=x3-x
g(x)=x3+2x2-10
So ​(f+g)(x) =  ?

2.
f(x)=x2+2x-6
g(x)=x4+3
So (f*g)(x) = ?

3.
f(x)=x4-x2+9
g(x)=x3+3x2+12
So (f-g)(x) = ?

 
Guest Apr 14, 2018
edited by Guest  Apr 14, 2018
edited by Guest  Apr 14, 2018
Sort: 

1+0 Answers

 #1
avatar+17721 
0

1)  (f + g)(x)  =  (x3 - x) + (x3 + 2x2 - 10)  =  (x3 + x3) + 2x2 - x - 10  =  2x3 + 2x2 - x - 10

 

2)  (f * g)(x)  =  (x2 + 2x - 6)(x4 + 3)  =  x6 + 2x5 - 6x4 + 3x2 + 6x -18)                    [distributive property]

 

3)  (f - g)(x)  =  (x4 - x2 + 9) - (x3 + 3x2 + 12)  =  x4 - x2 + 9 - x3 - 3x2 - 12  =  x4 - x3 - 4x2 - 3

 
geno3141  Apr 15, 2018

20 Online Users

avatar
avatar
avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details